IL-8 –251T/A and IL-12B 1188A/C polymorphisms are associated with gout in a Chinese male population. (March 2013) - Liu, S; Yin, C; Chu, N; Han, L; Li, C
Abstract : Objectives: Gout is caused by monosodium urate (MSU) crystal-induced inflammation of the joints and periarticular tissues. MSU crystals activate NALP3 and mediate interleukin (IL)-1β generation from its inactive pro-form, resulting in cellular activation and an IL-8-mediated neutrophil influx into the joint. IL-8 and IL-12 are important chemokines related to the initiation and amplification of acute and chronic inflammatory processes. In this study, we investigated whether the IL-8 –251T/A and IL-12 1188A/C polymorphisms are associated with susceptibility to gout in a Chinese Han male population. Methods: Overall, 387 patients with gout and 576 controls were included in this study. Genotyping was performed by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP). An association analysis was carried out using the χ 2 test. A genotype–phenotype analysis was also conducted. Results: The T allele of IL-8 –251 was associated with risk of gout [p = 0.031 (odds ratio (OR) 1.229, 95% confidence interval (CI) 1.019–1.483]. There was a clear link between the IL-12 1188 AA and AC genotypic and A allelic frequencies between gout cases and controls (p < 0.001, df = 2 by genotype; p < 0.001, OR 1.404, 95% CI 1.165–1.691 by allele). Conclusions: Our results suggest that the IL-8 –251T/A and IL-12B 1188A/C polymorphisms may be relevant host susceptibility factors for the development of gout.